2019
DOI: 10.1002/ccd.28379
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular iliac artery lithotripsy to enable transfemoral thoracic endovascular aortic repair

Abstract: Thoracic endovascular aortic repair (TEVAR) is performed with large‐bore delivery systems. Small‐size access vessels may be a contraindication for TEVAR, particularly in case of severe calcifications. In this case report, we describe the first‐in‐man use of intravascular lithotripsy to enable transfemoral delivery of TEVAR stent grafts in a patient with severely calcified iliac arteries. A 69‐year‐old female with multiple sclerosis and thoracic aortic aneurysm (TAA) was referred for percutaneous TEVAR. Both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…IVL was used to improve vessel compliance and predilection before stent placement[ 16 ]. Several authors reported the use of IVL for severely calcified vessels before stent placement[ 16 , 19 ] or before treatment with drug-coated balloon angioplasty[ 20 ]. IVL was also used in severely calcified vessels as a stand-alone treatment without stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…IVL was used to improve vessel compliance and predilection before stent placement[ 16 ]. Several authors reported the use of IVL for severely calcified vessels before stent placement[ 16 , 19 ] or before treatment with drug-coated balloon angioplasty[ 20 ]. IVL was also used in severely calcified vessels as a stand-alone treatment without stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…3 Intravascular lithotripsy (IVL) has emerged as a safe and effective option in the treatment of severely calcified vessels. [4][5][6][7] The principal mechanism of lithotripsy has been used in medicine for over 30 years in the treatment of nephrolithiasis, cholelithiasis, and joint calcifications.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupt CAD III will have a 2-year follow-up period and will provide long-term clinical outcome data to assess the efficacy of improved stent insertion after intracoronary IVL use. This study included patients with unstable coronary syndromes, ostial or bifurcation coronary lesions, treatment of in-stent restenosis or underexpanded coronary stents, 22 , 23 , 24 , 25 extreme calcification in upper extremity vessels (ie, carotid, subclavian/axillary, innominate) and vein grafts, as well as the infrarenal aorta, radial, and brachial arteries. After obtaining U.S. Food and Drug Administration approval of the Shockwave Coronary IVL System, an investigator-sponsored all-comers registry is currently enrolling in Spain (REPLICA [Registry of Coronary Lithotripsy in Spain; NCT04298307 ]; n = 400), and postmarket consent research is being evolved to use the American College of Cardiology National Cardiovascular Data Registry CathPCI Registry to provide perspectives into device safety and effectiveness in an expanded real-world setting.…”
Section: Future Directionsmentioning
confidence: 99%